Модель результативного ринку і технологія вантажних залізничних перевезень - Кузєв, І. О.; Kuziev, І. (ЦНТУ, 2022)
Процеси лібералізації, спроба переходу залізничної галузі на нову модель ринку вільної конкуренції без відповідних змін складової моделі негативно позначаються на ефективності роботи залізничної галузі та на результативності ринку вантажного залізничного сервісу. Пропонується поглянути на проблему не з позицій зміни форми власності в галузі та формування ринку вільної конкуренції, а з позиції пошуку рівноваги технології роботи та моделі ринку вантажних залізничних перевезень, що застосовується. Дослідження ґрунтується на відомій концепції Industrial organization. Результативність ринку вантажних залізничних перевезень багато в чому залежить від технології створення залізничного вантажного сервісу. Пропонується сформувати ринкову модель орієнтуючись не так на вигляд конкуренції, але в деяку гармонію технології вантажного залізничного сервісу та ринку, точніше рівноваги складових сервісного ринку. За результатами дослідження можуть бути сформульовані рекомендації щодо формування збалансованої моделі ринку вантажних залізничних перевезень та коригування цілей та існуючої моделі ринку. The processes of liberalization, the attempt to transition the railway industry to a new market model of free competition without corresponding changes in the component model negatively affect the efficiency of the railway industry and the effectiveness of the freight railway service market. It is proposed to look at the problem not from the standpoint of changing the form of ownership in the industry and the formation of a free competition market, but from the standpoint of finding a balance between the work technology and the model of the freight rail transport market that is being used. The study is based on the well-known concept of Industrial organization. The author considers the market as a living mechanism that responds to changes in its components within its field, not only as a place for concluding deals. The effectiveness of the rail freight transport market largely depends on the technology of creating a rail freight service. It is proposed to form a market model based not so much on the appearance of competition, but on some harmony of the technology of freight railway service and the market, or rather the balance of the components of the service market. The goal is to define a model of an effective rail freight market, in which the railway industry will be able to show maximum efficiency. Work methods – expert assessment of an attempt to change the model of the freight rail transportation market; analysis of the reasons for the imbalance of the economic mechanism of transport activity in the field of freight rail transport; an attempt to structure the goals of an efficient rail freight market. Based on the results of the research, recommendations can be formulated regarding the formation of a balanced model of the market for freight rail transportation and the adjustment of goals and the existing market model.
Result MarkeT Model and Railway Truck Transport Technology
Keywords: поле ринку; учасник процесу; вантажні залізничні перевезення; технологія перевізного процесу; market field; participant in the process; freight railway transportation; transportation process technology